The ‘Ilm Al-Qur'an: A Study of Asbab An-Nuzul, Makkiyyah and Madaniyyah - Ahmad Zainal Mustofa; Nurus Syarifah (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2024)
This paper attempts to explain the study of the Qur'anic Sciences about asbab an-nuzul, makkiyyah and madaniyyah. This research was conducted to determine the characteristics and benefits of studying the three branches of knowledge in the ‘Ulum Al-Qur'an. After doing the research, it can be concluded that the Al-Qur'an was revealed to the Arab community which is thick with their ancestral culture. Some of the verses of the Al-Qur'an must be understood by looking at the background of the revelation of the verse. There is a correlation in asbab an-nuzul, makkiyyah and madaniyyah which as the cause of the revelation of a verse in the Al-Qur'an is called asbab an-nuzul. Then for the time of the revelation of a verse is divided into two, namely makkiyyah and madaniyyah. Both makkiyyah and madaniyyah have asbab an-nuzul in the time of the revelation of the verse. Then by studying the three branches of ‘Ulum Al-Qur’an, we can increase our faith in the Al-Qur'an which is the word of Allah SWT.